Analisis pengendalian kualitas produksi Calzone menggunakan metode Six Sigma dan Failure Mode Effect Analysis (FMEA) Pada PT. XYZ - Dewantoro, I Made Benito Markus Lucky; Wiranatha, Anak Agung Putu Agung Suryawan; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
PT. XYZ, a company in the pastry and bakery industry, is facing production challenges with its calzone product, which had the highest defect rate at 1.01% out of 4,547 units produced in November 2024, leading to potential financial losses. This study aims to develop a quality control strategy using the Six Sigma method through the stages of Define, Measure, Analyze, and Improve, with the improvement stage utilizing the FMEA method to identify potential causes of defects and provide corrective strategies. The results show that the average sigma level for calzone products is 3.28, which is still far from the ideal level of six. The two main types of defects found are burnt products and incorrect shapes, each caused by different factors. The highest RPN of 210 is associated with the cause of machines not functioning properly. To address this issue, it is recommended that the company hire additional engineering staff to ensure proper machine operation and regular maintenance, as well as provide training for employees who lack understanding in the dough shaping process.